Understanding Problem Fermentations – A Review - Malherbe, S.; Bauer, F.F.; du Toit, M. (South African Journal of Enology and Viticulture, 2016)
Despite advances in winemaking technology and improvements in fermentation control, problem alcoholic and malolactic fermentations remain a major oenological concern worldwide. This is due to possible depreciation of product quality and its consequent negative economic impact. Various factors have been identified and studied over the years, yet the occurrence of fermentation problems persists. The synergistic effect of the various factors amongst each other provides additional challenges for the study of such fermentations. This literature review summarises the most frequently studied causes of problematic alcoholic and malolactic fermentations and in addition provides a summary of established and some potential new analytical technologies to monitor and investigate the phenomenon of stuck and sluggish fermentations.